Neurocognitive correlates of the effects of yoga meditation practice on emotion and cognition: a pilot study - Froeliger, Brett; Garland, Eric L.; Modlin, Leslie A.; McClernon, F. Joseph (Frontiers in Integrative Neuroscience, 2012)
Mindfulness meditation involves attending to emotions without cognitive fixation of emotional experience. Over time, this practice is held to promote alterations in trait affectivity and attentional control with resultant effects on well-being and cognition. However, relatively little is known regarding the neural substrates of meditation effects on emotion and cognition. The present study investigated the neurocognitive correlates of emotion interference on cognition in Yoga practitioners and a matched control group underwent fMRI while performing an event-related affective Stroop task. The task includes image viewing trials and Stroop trials bracketed by neutral or negative emotional distractors. During image viewing trials, Yoga practitioners exhibited less reactivity in right dlPFC to negative as compared to neutral images; whereas the control group had the opposite pattern. A main effect of valence (negative > neutral) was observed in limbic regions (e.g. amygdala), of which the magnitude was inversely related to dlPFC activation. Exploratory analyses revealed that the magnitude of amygdala activation predicted decreased self-reported positive affect in the Control group, but not among Yoga practitioners. During Stroop trials, Yoga practitioners had greater activation in vlPFC during Stroop trials when negative, compared to neutral, emotional distractor were presented; the control group exhibited the opposite pattern. Taken together, these data suggest that though Yoga practitioners exhibit limbic reactivity to negative emotional stimuli, such reactivity does not have downstream effects on later mood state. This uncoupling of viewing negative emotional images and affect among Yoga practitioners may be occasioned by their selective implementation of frontal executive-dependent strategies to reduce emotional interference during competing cognitive demands and not during emotional processing per se.